(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2016)
Research of insect of community structure on coffe (Coffea robusta L.) in Belimbing Village Muara Pinang Subdistrict Sumatera Selatan Province, conducted September till October 2013, to saw insect species of coffe plant, density, ferquency, importan value index and diversity index. The research used direct survey method, and data sampling with purpossive in transect. The result showed gated 15 species insects are Valanga nigricornis, Anax sp, Neoconocephalus sp, Oecopylla smaragdina, Gryllus miratus, Hydrophilus sp, Photuris sp, Zizinia sp, Mantis sp, Phyllophaga sp, Hypothenemus hampei, Bactrocera conformis, Sexava sp, Tipula sp and Polistes sp. Oecopylla smaragdina was dominant species, with importan value index 34,94%Diversity index was medium categhory with H’ value 2,22. Key words : diversity, insect, Vigna sinensis